Understanding the Concept of Fraud, Corruption and Financial Frauds in India: Examining the Impact of Economic Scams and Financial Frauds on India's Growth (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Economic scams are a global phenomenon and have serious implications and consequences for the growth of economy of the country. There is a wide spread perception that the level and pervasiveness of economic scams are gaining significance. Post liberalization the economy of the country started to gain momentum due to integration of the country’s economy with the world economy. A quantum leap was witnessed in various sectors such as Industrial sector Manufacturing sector, Services sector and even the Public sector. The mission of CBI is to uphold the Constitution of India and law of the land through in-depth investigation and successful prosecution of offences to provide leadership and direction to police forces and to act as the Nodal Agency for enhancing inter-state and international cooperation in law enforcement. The vision of CBI is based on motto, mission and the need to develop professionalism, transparency, adaptability to change and use of science and technology in our working. Primary functions of CBI is to assist in the investigation of crimes such as murder, kidnapping and terrorism. In this Article we studied an overview on Fraud, Corruption and underlined the cases of Financial Frauds in India.